Note on Mechanism for Formation of Bulbs (Structures) in Complex Plasmas with Grains of Different Size. Issue 6 (1st April 2015) - Tsytovich, V.; Suetterlin, R.; Thomas, H.; Ivlev, A.
Abstract In this note the phenomena of formation of grain bulbs (compact grain structure) in presence of grains with different size is discussed from point of view of grain force balance. The requirement is found showing where in the equilibrium conditions the larger size grains are expelled from the regions of smaller size grains forming dust bulbs containing only the smallest size grains. The experiments where this phenomenon was observed are discussed. It is possible to conclude that these experiments can serve as direct evidence for existence of the non‐linear screening of individual grains and for excitation of collective large scale electric fields that balances the drag forces in domain of structures. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)